2005
DOI: 10.1063/1.2008357
|View full text |Cite
|
Sign up to set email alerts
|

Photonic crystal with diamondlike structure fabricated by holographic lithography

Abstract: In this letter, we report a diamondlike structure. Our theoretical analysis reveals that a large complete band gap exists between the second and third bands with only a very low refractive index is needed (n⩾2.05) to open the complete band gap for this inverse structure. Large-scale and high-quality three-dimensional structures with this diamondlike symmetry are fabricated by a holographic lithography method using four laser beams incident from the same half-space. The beam geometry is similar to that for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…By optimizing the photoresist initiation system, they observed that the measured peak reflectance is 70%, which is significantly higher than that of typical fabricated crystals and only about 30% for common polymeric templates [33,40,104,105,114].…”
Section: The Band Characteristics Of Pcs Made By Photoresistmentioning
confidence: 97%
See 2 more Smart Citations
“…By optimizing the photoresist initiation system, they observed that the measured peak reflectance is 70%, which is significantly higher than that of typical fabricated crystals and only about 30% for common polymeric templates [33,40,104,105,114].…”
Section: The Band Characteristics Of Pcs Made By Photoresistmentioning
confidence: 97%
“…To achieve CBGs in PCs made by the photoresist, i.e., to increase the refractive index contrast to 2 or more [36][37][38][39][40], there are two feasible solutions. i) PCs made by the photoresist can be used as templates for the production of inverse replica structures, for example, by filling the void with high refractive index and burning out or dissolving it [20,23,[102][103][104][105] and ii) by doping metal nanoparticles in the photoresist [94,[106][107][108][109].…”
Section: Improvement Of Holographic Recording Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…In the late 1990s, interference lithography was used to produce 2D [158] PC lattices exhibiting a photonic bandgap and later 3D face-centered cubic [157] PC structures as depicted in Figure 7(a). Since then, MBIL has been extensively studied, optimized, and used to fabricate PCs [109,184,[198][199][200][201][202][203] with ongoing efforts to develop PC-based devices through a combination of lithography techniques such as the PC waveguide depicted in Figure 7(b). In fact, the design rules for MBIL-defined PC waveguide devices have been theoretically defined, when interference lithography is combined with direct laser writing [204].…”
Section: Photonic Crystalsmentioning
confidence: 99%
“…2,3 Several groups have reported approaches to fabricating three-dimensional photonic crystals to achieve photonic band gaps ͑PBGs͒ with defect doping for in-PBG mode control and waveguiding. [4][5][6][7][8][9] The ability to dynamically tune the properties of photonic crystal ͑PC͒ devices by manipulating the dielectric contrast through the incorporation/infiltration of liquid crystals ͑LCs͒ has been explored by several groups as well. 10,11 Many applications in active photonic devices, such as displays, switches, and dynamic lenses, provide a strong motivation to further enhance and develop approaches to dynamic tunability.…”
mentioning
confidence: 99%